Split median superficial sural artery perforator (MSSAP) flap and medial sural artery perforator (MSAP) flap for posterior thigh sarcoma reconstruction. Issue 2 (5th February 2020) - Mazur, Natalia; Osinga, Rik; Lo, Steven
Abstract : Reconstruction of composite defects of the posterior thigh and knee is challenging. Pedicled medial gastrocnemius flaps are the traditional reconstructive approach, but late contractures related to skin grafted muscle may affect knee function. More recently, the medial sural artery perforator (MSAP) flap has been described for such defects, although may necessitate skin grafting of the donor site. To minimise the drawbacks with these options, we describe a combination of a median superficial sural artery perforator (MSSAP) flap and MSAP flap. This allows both tension free closure of the donor site without skin grafting, and facilitates coverage of a round defect by splitting the flap into two adjacent triangular flaps. This is the first report of posterior thigh defect reconstruction with a combination of MSSAP and MSAP flaps.